Beyond Formality in Indonesian Pretrial Law: KUHAP Reform, Human Rights, and Islamic Law - Irawati, Arista Candra; da Silva, Eugenia Brandao (Al-Ahkam, 2025)
Indonesia's pretrial system has long faced challenges, including formalistic procedures, limited judicial oversight, and potential violations of suspects' rights. The Constitutional Court Decision No. 21/PUU-XII/2014 expanded pretrial review, especially regarding suspect designation. Yet, gaps remain in implementation, legal certainty, and due process. This study aims to critically evaluate the reconfiguration of Indonesia's pretrial mechanism by integrating human rights principles, Islamic criminal law, and KUHAP reform. Employing doctrinal analysis of legislation, case law, and jurisprudence, complemented with comparative insights from Malaysia, Egypt, and Türkiye, the research examines how procedural fairness and accountability can be strengthened. Findings reveal persistent weaknesses in judicial control, repeated suspect status, and post factum review. Integrating positive law, human rights, and Islamic law principles such as ḥisba, qāḍī al-maẓālim, al-bayyina, and dar’ al-ḥudūd bi al-shubuhāt can enhance procedural justice. Recommendations include clearer pretrial codification, substantive judicial oversight, and adoption of Islamic law insights to build a more equitable, rights-oriented pretrial framework in Indonesia.